BIRDS EYE 4-70, 22 September-7 October 1970. - Freeman,R. F.; Rankin,R. D. (1971)
BIRDS EYE 4-70 was a regularly scheduled Arctic Ocean ice reconnaissance mission covering the North American sector of the Arctic Ocean including Baffin Bay and Davis Strait between 22 September and 7 October 1970. Ice was observed under daylight or twilight conditions. Weather conditions were generally good, except north of Greenland and west of Prince Patrick and Banks Islands. Remnant ice with noted refreezing was observed in Baffin Bay. An extensive area of new ridges existed northwest of Ellesmere Island. Severe ice conditions existed in the Alaskan area. The ice was photographically mapped at several locations. (Author)